The Relationship Between Nutritional Status (BMI) And Stress Levels on Physical Fitness of Extracurricular Sports Students - Liverti, Dona Puspa; Manullang, Jujur Gunawan; Hermansah, Bambang (Journal of Social Work and Science Education, 2023)
This study aimed at analyzing the relationship between nutritional status (BMI) and stress levels on the physical fitness of extracurricular students of SMAN 1 OKU. This research was conducted on extracurricular sports students at SMAN 1 OKU. The research used in this study is quantitative. The research method uses path analysis techniques. The population of this study was all sports extracurricular students at SMAN 1 OKU. The number of samples in this study amounted to 112 people aged 15-17 years. The instruments in this study were to measure BMI through weight and height measurements, physical fitness using the VO2Max test and to measure stress levels using questionnaires. The data analysis technique used is a path analysis technique. The results of the analysis of the relationship between BMI and stress level using the chi-square test showed a p-value = 0.737. Based on the results of the analysis, it can be seen that the p-value≥ 0.05 which means there is no relationship between nutritional status BMI and stress levels in extracurricular students at SMAN 1 OKU. The results of the analysis of the relationship between BMI and physical fitness of extracurricular students obtained a value of 0.039 or p< 0.05 which means that there is a significant relationship between BMI and physical fitness. The conclusion is that there is no relationship between nutritional status BMI and stress levels, but there is a significant relationship between BMI and the physical fitness of extracurricular students of SMAN 1 OKU.